(untitled) (Journal of the College of Basic Education, 2026)
This study aims to explore the relationship between fear of loss and cognitive failure among middle school students. The descriptive-analytical method was applied using a questionnaire tool consisting of two dimensions, with each dimension containing 10 questions to measure both fear of loss and cognitive failure. The sample consisted of 200 middle school students from Al-Fadhila Secondary School in the first education district of Karkh . The study found statistically significant results indicating a relationship between the level of fear of loss and cognitive failure among students. The results showed that students with high levels of fear of loss tended to score lower in academic performance tests, suggesting that psychological fear affects their ability to focus and achieve academically. The results also indicated differences in the impact of fear of loss among students based on factors such as gender and academic specialization, with clear distinctions between male and female students in levels of fear of loss and cognitive failure. The study recommended the development of awareness and psychological counseling programs to help students manage feelings of fear of loss and improve their academic performance through effective learning techniques and psychological support methods. It also called for the inclusion of educational strategies that help students build self-confidence and enhance their time management and academic pressure management skills.